Effect of Suji Leaf Ethanolic Extract (Dracaena angustifolia) on The Sperm Motility of Mice (Mus musculus) Exposed to Cigarette Smoke - Hakim, Muhammad Alfianul; Bahri, Syamsul; Lestari, Tri Ayu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Cigarette smoke exposure can induce oxidative stress, leading to reduced sperm motility. Suji leaves contain antioxidants, including flavonoids, alkaloids, terpenoids, and steroids. This study aims to determine the effect of cigarette smoke exposure on mouse sperm motility and the effect of suji leaf ethanolic extract on the sperm motility of mice exposed to cigarette smoke. This study employed an experimental research design using a factorial Completely Randomized Design (CRD) involving 48 mice. Two factors were combined in the treatment groups: the duration of cigarette smoke exposure (0, 5, 15, and 30 minutes) and the dose of suji leaf ethanolic extract (0, 250, 500, and 750 ppm). Sperm motility was assessed using a hemocytometer under a light microscope at 400× magnification. Data were analyzed using a two-way analysis of variance. The results of statistical analysis indicated that cigarette smoke exposure had a significant effect on mouse sperm motility (0.000 < 0.05), and that suji leaf ethanolic extract significantly affected the sperm motility of mice exposed to cigarette smoke (0.036 < 0.05). These results indicate that cigarette smoke exposure can reduce sperm motility, and the administration of suji leaf ethanolic extract is able to increase and improve the sperm motility of mice caused by cigarette smoke exposure. Thus, suji leaf ethanolic extract can serve as a natural antioxidant to improve sperm motility affected by cigarette smoke exposure.